2016
DOI: 10.1091/mbc.e16-03-0185
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin-related Smy1 enhances the Rab-dependent association of myosin-V with secretory cargo

Abstract: Smy1 is a kinesin-related protein that enhances the association of the Myo2 myosin-V motor with its receptor, the Rab Sec4, on secretory vesicles. This function requires Smy1’s head, coiled-coil, and tail domains and is specific for secretory vesicle transport but not for mitochondrial segregation by Myo2, which also uses a Rab protein, Ypt11.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…A plausible explanation might be that these cargo adaptors contain multiple Myo2-binding sites. Consistently with this explanation, the central coiled-coil region of Smy1 was also reported to bind with Myo2 (24). Although the Inp2-binding site was mapped onto subdomain-I of Myo2-GTD in our work (Fig.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…A plausible explanation might be that these cargo adaptors contain multiple Myo2-binding sites. Consistently with this explanation, the central coiled-coil region of Smy1 was also reported to bind with Myo2 (24). Although the Inp2-binding site was mapped onto subdomain-I of Myo2-GTD in our work (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…Smy1 was first reported to be a kinesin-like protein, which suppresses a temperature-sensitive phenotype of cells carrying a motility-deficient mutation in Myo2 (22,28). By interacting with both actin and Myo2, Smy1 enhances the motility of Myo2 (29) and cooperates with Sec4 in transporting secretory vesicles (24). The Myo2-interacting site (MIS) in Smy1 was mapped onto its C-terminal region (25) ( Fig.…”
Section: Smy1 Occupies a Hydrophobic Groove In Myo2-gtdmentioning
confidence: 99%
See 1 more Smart Citation
“…An essential function of the yeast myosin-V motor encoded by MYO2 is to transport secretory vesicles to the site of cell growth (Johnston et al, 1991;Schott et al, 1999). The kinesin-related protein Smy1 functions with Myo2 to enhance the association of Myo2 with its receptor on secretory vesicles, the Rab Sec4 (Beningo et al, 2000;Lillie and Brown, 1994;Lwin et al, 2016). We have described myo2 mutant alleles partially compromised in binding Sec4 in which SMY1 becomes essential and used these alleles to generate myo2 smy1 conditional mutations ( Figure 1A and B).…”
Section: Resultsmentioning
confidence: 99%
“…The transport of secretory vesicles by Myo2 is an essential process which has been shown genetically to involve the non-essential kinesin-related protein Smy1 Brown, 1994, 1992). Smy1 interacts directly with Myo2, and we have previously shown that it functions to specifically enhance the association of Myo2 with the secretory vesicle receptor, Sec4 (Lwin et al, 2016;Lillie and Brown, 1994). In this report, we employ a genetic approach to uncover additional components that may be involved in the direct or indirect regulation of secretory vesicle transport.…”
Section: Introductionmentioning
confidence: 99%